The Better Survival of MSI Subtype Is Associated With the Oxidative Stress Related Pathways in Gastric Cancer - Cai, Lei; Sun, Yeqi; Wang, Kezhou; Guan, Wenbin; Yue, Juanqing; Li, Junlei; Wang, Ruifen; Wang, Lifeng (Frontiers in Oncology, 2020)
Background: Gastric cancer (GC) is the third leading fatal cancer in the world and its incidence ranked second among all malignant tumors in China. The molecular classification of GC, proposed by the The Cancer Genome Atlas (TCGA), was added to the updated edition(2019) of WHO classification for digestive system tumor. Although MSI and EBV subtypes appeared as ever-increasingly significant roles in immune checkpoint inhibitor therapy, the underlying mechanisms are still unclear. Methods: We systematically summarized the relationship between EBV, d-MMR/MSI-H subtypes and clinicopathological parameters in 271 GC cases. Furthermore, GSE62254/ACRG and TCGA-STAD datasets, originated from Gene Expression Omnibus(GEO) and TCGA respectively, were analyzed to figure out the prognosis related molecular characteristics by bioinformatics methods. Results: Patients with MSI subtype had better prognosis than the MSS subtype (P=0.013) and considered as an independent biomarker by the univariate analysis (P=0.017) and multivariate analysis (P=0.050). While there was no significant difference between EBV positive and negative tissues (P=0.533). The positive prognostic value conferred by MSI in different cohorts were revalidated via the clinical analysis of GSE62254/ACRG and TCGA-STAD datasets regardless of race. Then key gene module that tightly associated with better status and longer OS time for MSI cases was obtained from weighted gene co-expression network analysis(WGCNA). NUBP2 and ENDOG were screened from the gene cluster and oxidative phosphorylation, reactive oxygen species(ROS) and glutathione metabolism were analyzed to be the differential pathways in their highly expressed groups. Conclusions: Our results manifested the significant prognostic value of MSI in Chinese GC cohort and comparisons with other populations. More opportunities to induce apoptosis of cancer cells, led by the unbalance between antioxidant system and ROS accumulation, lay foundations for unveiling the better prognosis in MSI phenotype through the bioinformatics analysis.